2018
DOI: 10.3390/su10124603
|View full text |Cite
|
Sign up to set email alerts
|

Analysis on Consumers’ Purchase and Shopping Well-Being in Online Shopping Carnivals with Two Motivational Dimensions

Abstract: The development of online shopping carnivals (OSCs) is in full bloom due to the support of logistics industry and information technology. More and more people are keen to participate in them. This study contributes to literature by exploring the role of motivational factors (based on utilitarian and hedonic shopping values dimension) of the intention to participate in the actual purchase behavior of consumers and their shopping well-being in OSC. A model is developed and tested to explain consumers’ shopping p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
38
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(57 citation statements)
references
References 39 publications
3
38
0
4
Order By: Relevance
“…Hedonic and utilitarian shopping values are an active research area in e-commerce. In their study of e-commerce consumers' purchase and shopping well-being, Yu et al ( 2018 ) investigated the role of hedonic and utilitarian shopping values on the intention of consumers to purchase in shopping carnivals held online. The authors concluded that people with hedonic shopping values are persuaded by entertainment while those with utilitarian shopping values are influenced by saving money, selection, and convenience.…”
Section: Related Workmentioning
confidence: 99%
“…Hedonic and utilitarian shopping values are an active research area in e-commerce. In their study of e-commerce consumers' purchase and shopping well-being, Yu et al ( 2018 ) investigated the role of hedonic and utilitarian shopping values on the intention of consumers to purchase in shopping carnivals held online. The authors concluded that people with hedonic shopping values are persuaded by entertainment while those with utilitarian shopping values are influenced by saving money, selection, and convenience.…”
Section: Related Workmentioning
confidence: 99%
“…In their study, Chakraborty ve Soodan (2019) suggested that convenience, monetary savings and selection affect the utilitarian value positively and entertainment and social status affect the hedonic value positively. In another study, Yu et al (2018) found that convenience, selection and monetary saving affects the utilitarian value positively. In the study, it was determined that hedonic and utilitarian values affect satisfaction positively.…”
Section: Discussing the Findings With The Literaturementioning
confidence: 95%
“…Since buying is a continuous process, an anticipation of purchase also evokes positive emotions, however, relatively fewer researches have focused on the relationship between purchase intentions and well-being . In separate studies, intention to shop and intention to participate in online shopping carnivals were seen as a predictors of consumer well-being for segments other than BoP (Papagiannidis, Bourlakis, Alamanos, & Dennis, 2017;Yu, Zhang, & Liu, 2018).…”
Section: Non-essential Purchases and Subjective Well-beingmentioning
confidence: 99%